On the key equation - Fitzpatrick, P. (IEEE transactions on information theory, 1995)
A study was undertaken to derive algorithms for solving a general key equation from a unified and conceptually simple theoretical standpoint. A decoder designed to implement one of the algorithms should be at least as good as its classical counterpart.